About Neosyncretism of the Subject Organization of the Russian Lyrics of the Beginning of the 20th Century (On Poetry Material of A. Akhmatova, M. Tsvetaeva, A. Barkova) - Локтевич, Екатерина (Literatūra, 2016)
In the article, the reasons of the individualization of the subject organization of the Russian lyrics of the beginning of the 20th century, showing the synthesis of different communicative strategy, are established. The typology of the subject organization of poetry of the period is located, the essence and the principles of the functioning of the phenomenon of an ideological and subject borderline are characterized. The analysis of poems of A. Akhmatova, M. Tsvetaeva and A. Barkova shows the role of neosyncretism in the formation of variations of the subject–object relations.
Keywords: lyrics; subject organization; communicative strategy; subject–object relations; borderline